Inhibition of Autophagy Enhances Sunitinib-Induced Cytotoxicity in Rat Pheochromocytoma PC12 cells - Tatsuhiko Ikeda; Kiyo-aki Ishii; Yuria Saito; Masahiro Miura; Aoi Otagiri; Yasushi Kawakami; Hitoshi Shimano; Hisato Hara; Kazuhiro Takekoshi (Elsevier, 2013)
Sunitinib is an oral multitargeted receptor tyrosine kinase inhibitor with antiangiogenic and antitumor activity that mainly targets vascular endothelial growth factor receptors, and recently, it has been shown to be an active agent for the treatment of malignant pheochromocytomas. Previously, we demonstrated that sunitinib directly inhibited mTORC1 signaling in rat pheochromocytoma PC12 cells. Although autophagy is a highly regulated cellular process, its relevance to cancer seems to be complicated. It is of note that inhibition of mTORC1 is a prerequisite for autophagy induction. Indeed, direct mTORC1 inhibition initiates ULK1/2 autophosphorylation and subsequent Atg13 and FIP200 phosphorylation, inducing autophagy. Here, we demonstrated that sunitinib significantly increased the levels of LC3-II, concomitant with a decrease of p62 in PC12 cells. Following sunitinib treatment, immunofluorescent imaging revealed a marked increased punctate LC3-II distribution. Furthermore, Atg13 knockdown significantly reduced its protein level, which in turn abolished sunitinib-induced autophagy. Moreover, inhibition of autophagy by siRNAs targeting Atg13 or by pharmacological inhibition with ammonium chloride, enhanced both sunitinib-induced apoptosis and anti-proliferation. Thus, sunitinib-induced autophagy is dependent on the suppression of mTORC1 signaling and the formation of ULK1/2-Atg13-FIP200 complexes. Inhibition of autophagy may be a promising therapeutic option for improving the anti-tumor effect of sunitinib. Keywords:: autophagy, sunitinib, pheochromocytoma, genetic ablation, pharmacological autophagy inhibitor